2020
DOI: 10.1177/1120672120976550
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Mustardè cheek advancement flap and paramedian forehead flap as a reconstructive option in orbital exenteration

Abstract: Purpose: To describe a combinatory technique made of Mustardè cheek advancement flap and paramedian forehead flap as a reconstructive option after orbital exenteration. Methods: We retrospectively reviewed all patients who underwent orbital exenteration and subsequent reconstruction with this technique at our Head and Neck Department, Divisions of Ophthalmology and Otolaryngology, at San Raffaele Hospital, Milan, Italy. Results: Three patients were treated with the aforementioned technique, following orbital e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
0
14
0
3
Order By: Relevance
“…This approach varies according to tumor size, depth, and location. It allows the microscopic examination of the entire surgical margins during surgery so that the extent of excision can be defined precisely [ 8 ]. In our case, we used a 10 mm strip margin with a double scalpel blade to ensure the quality of the biopsy sample and, subsequently, the oncological results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach varies according to tumor size, depth, and location. It allows the microscopic examination of the entire surgical margins during surgery so that the extent of excision can be defined precisely [ 8 ]. In our case, we used a 10 mm strip margin with a double scalpel blade to ensure the quality of the biopsy sample and, subsequently, the oncological results.…”
Section: Discussionmentioning
confidence: 99%
“…The second flap was a cheek rotational (Mustardé) flap designed in the 1960s. Some studies [ 8 , 10 ] mentioned that the combination of both flaps has a significant benefit in closing large defects in terms of mobility of mid and lateral cheek due to the unique features of the skin, excellent color and texture match, wide-based pedicle flap with appropriate vascularity and good aesthetic outcome. A large study of 116 patients demonstrated a low rate of recurrence of BCC in those cases where flaps and grafts were used in the surgical reconstruction with pre-established margins by the conventional method [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck tumors often need a reconstructive phase with pedicled or free flaps after the ablative surgery 1–6 . Some pedicled flaps, such as the supraclavicular flap or the paramedian forehead flap (PFF), may require a second‐stage pedicle division and inset after the initial harvesting, a procedure consisting of pedicle division generally performed at least 3 weeks after the former one to let flap inosculation occur 7 …”
Section: Introductionmentioning
confidence: 99%
“…Head and neck tumors often need a reconstructive phase with pedicled or free flaps after the ablative surgery. [1][2][3][4][5][6] Some pedicled flaps, such as the supraclavicular flap or the paramedian forehead flap (PFF), may require a second-stage pedicle division and inset after the initial harvesting, a procedure consisting of pedicle division generally performed at least 3 weeks after the former one to let flap inosculation occur. 7 Several techniques are commonly used for perfusion assessment of the flaps, including simple visual observation, Doppler ultrasound, tissue oximetry, and indocyanine green (ICG) fluorescence video-angiography.…”
Section: Introductionmentioning
confidence: 99%
“…4 Many surgeons try to create their own standard method using the method they find safe or a combination of various methods. 6 - 11 The first reported surgical approach was by Dieffenbach in 1845. 12 The aim of the surgery is to create a natural antihelix and conchal cartilage and to correct the concomastoid angle.…”
Section: Introductionmentioning
confidence: 99%